Effect of Lime and Integrated Nutrient Management on Rice-pea Cropping System - Ao, Arenjungla; Kithan, Lowrence; Longkumer, L. Tongpang (International Journal of Bio-resource and Stress Management, 2021)
The field experiment was conducted to study the individual and synergistic effects of lime, NPK and manure application on rice–pea productivity during the kharif and rabi seasons of 2016–17 and 2017–18 from June to January in the experimental farm of SASRD, Nagaland University, Nagaland State, India. The experiment was laid out in Factorial Randomized Block Design with two levels of lime viz. without lime, Lime @ 2 q ha-1 and four levels of integrated nutrient management viz. Recommended Dose of Fertilizers, Recommended Dose of Fertilizers (75%)+Farm Yard Manure @ 6 t ha-1, Recommended Dose of Fertilizers (75%)+Poultry manure @ 1 t ha-1 and Recommended Dose of Fertilizers (75%)+Azospirillum+Phosphorus Solubilizing Bacteria and replicated thrice. Results revealed that the application of lime @ 2 q ha-1 brought about a significant increase in the growth and yield attributes of rice and pea. Among the nutrient sources, the application of Recommended Dose of Fertilizers (75%)+Farm Yard Manure@ 6 t ha-1 proved superior in terms of growth and yield over other treatments. With regard to economics like gross return ha-1, net return ha-1, benefit-cost ratio, system productivity and Rice Equivalent Yield (REY) treatment interactions of lime @ 2 q ha-1 and Recommended dose of fertilizers (75%)+farm yard manure @ 6 t ha-1 performed better by recording the highest.